2021
DOI: 10.23887/jet.v5i1.32314
|View full text |Cite
|
Sign up to set email alerts
|

Development of Learning Videos Based on Problem-Solving Characteristics of Animals and Their Habitats Contain in Ipa Subjects on 6th-Grade

Abstract: Lack of available learning media in the form of videos in a bold learning process during the Covid-19 pandemic, so that it has not been able to attract students' attention while studying. This study aimed to develop a learning media video based on problem-solving in IPA subjects, and its feasibility has been tested according to expert test evaluations and individual trials. The type of this research is a development using the ADDIE model. The method used to collect data was a questionnaire equipped with interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
58
0
64

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(128 citation statements)
references
References 19 publications
6
58
0
64
Order By: Relevance
“…Each meeting begins with presenting learning videos and examining the relationship between learning materials and ideas. Learning videos help students understand the material quickly (Andriyani & Suniasih, 2021;Priantini, 2020;Wisada, Sudarma, & Yuda S, 2019). At this stage, an integrative reconciliation process can occur.…”
Section: Resultsmentioning
confidence: 99%
“…Each meeting begins with presenting learning videos and examining the relationship between learning materials and ideas. Learning videos help students understand the material quickly (Andriyani & Suniasih, 2021;Priantini, 2020;Wisada, Sudarma, & Yuda S, 2019). At this stage, an integrative reconciliation process can occur.…”
Section: Resultsmentioning
confidence: 99%
“…With the motion and animation elements that video has, learning video can attract students' attention longer when compared to other learning media. Another advantage of video learning is that it overcomes the limitations of space and time, can be repeated, the message conveyed in the video is easy to remember, can train students' imagination, and foster student interest in learning (Andriyani & Suniasih, 2021;Febriani, 2017;Utari, 2016). In addition, this learning media also has a weakness; namely, the video is not suitable for topics where the study is detailed regarding a single visual that is involved and a fixed speed so that it cannot always be displayed in groups, some students may be left behind (Krishna et al, 2015;Naharir et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Teachers tend to utilize the lecture method in order to convey the learning content. In addition, teachers cannot design or employ learning media that is consistent with students' characteristics during the learning process (Andriyani & Suniasih, 2021;Khan & Masood, 2015;Putra & Sujana, 2020). The use of learning media in Indonesia has not been thoroughly carried out optimally by teachers.…”
Section: Introductionmentioning
confidence: 99%
“…The findings of related research regarding learning videos stated that learning videos could increase students' interest in learning (Andriyani & Suniasih, 2021;Kawka et al, 2021;Novita, Sukmanasa, & Pratama, 2019). Other research results also indicated that learning videos could assist students with learning problems to improve their learning outcomes.…”
Section: Introductionmentioning
confidence: 99%